Разработка модели выпрямителя с рекуперацией для группового питания электроприемников - Андриенко, Петр Дмитриевич; Климко, Александр Николаевич; Шрам, Алексей Анатольевич; Немыкина, Ольга Владимировна (НТУ "ХПИ", 2010)
Analytical study of the work 4Q-S converter is made In article in mode «transparent» and comparison result with the numerical modeling in Matlab/Simulink for the reason estimations of inaccuracy to models.
The development to models of the rectifier with recuperative for group power supply the electroreceiver
Keywords: привод асинхронный; привод частотно-регулируемый; преобразователь; инвертор; напряжение; мощность; конденсатор; нагрузка; сопротивление активное